Cómo ser joven y no morir en el proceso: hacia un modelo de vida de un joven con vacío existencial - Hernández González, Eduardo (2024)
Young people are a population group with a high incidence of anxiety and depression in the world and in Mexico and it increased during the confinement due to the COVID-2019 pandemic. This article shows the qualitative results of a mixed empirical study conducted during the school year 2022-A, in young students of the Centro Universitario de la Ciénega, University of Guadalajara, Mexico. The aim of the study was to describe the causes that young people attribute to the experience of existential emptiness, as well as the way they are feeling it and how they express it, and to explain by means of their own model the precursor and triggering events of existential emptiness. The sample consisted of 10 young students of the Bachelor’s Degree in Psychology, to whom the Purpose in Life Test (PIL) (Crumbaugh and Maholick 1969) was previously applied, which evaluates the degree of realization in which the students’ meaning of life is found, in their different contexts, and allows identifying those who are experiencing an existential void. Once identified, semi-structured interviews were conducted. The results show that young people with existential emptiness experience negative emotions and manifest it through risky behaviors whose consequences can be varied.